A comparative study of the utilisation of an electronic test–result management system in emergency and intensive care settings. (December 2020) - Thomas, Judith; Dahm, Maria R; Li, Julie; Westbrook, Johanna I; Georgiou, Andrew
The purpose of this qualitative study was to identify differences in the utilisation of an electronic medical record test–result management system between two acute care departments. Field observations (130 min) and semi-structured interviews (n = 24) were conducted in the Intensive Care Unit and Emergency Department of an Australian hospital. Work processes identified from audio transcripts were modelled using business process modelling. Comparison of the Emergency Department and Intensive Care Unit identified the following: (1) test ordering variations according to clinical roles, (2) differences in the use of electronic medical record functionality according to specific demands of the clinical environment and (3) the non-linear components of the test–result management process. Variations were identified in the number of process decisions, external collaborations and temporal process workflows. Modelling the business processes, collaboration and communication needs of individual clinical environments can aid in enhancing the quality and appositeness of health information technology interventions and thus contribute to improving patient safety. Future health information technology interventions/evaluations aimed at improving the safety of test–result management processes need to address both the nuances of the clinical environment and accommodate the individual work practices of clinicians within that environment.